The Relationship of Mother’s Knowledge to the Incidence of Stunting in Children at the Bromo Public Health Center, Medan Denai, Indonesia - Claudia Siregar, Grace Clara; Wienaldi; Wika Hanida Lubis (HM Publisher, 2023)
Stunting is a condition where there is a growth disorder in a child caused by a lack of intake of both macronutrients and micronutrients. A mother is an individual who is very close to a child regarding the growth and development of the child. This study aimed to determine the relationship between mother’s knowledge and the incidence of stunting in children at the Bromo Public Health Center, Medan Denai, Indonesia. Cross-sectional analytic observational study. A total of 62 respondents who were mothers of children aged 36-60 months were included in this study. Data analysis was carried out with the help of SPSS software in a univariate and bivariate to determine the relationship between mother’s knowledge and the incidence of stunting. The majority of children with stunting nutritional status have mothers with poor knowledge regarding nutritional intake. In conclusion, there is a statistical relationship between the mother's knowledge and the incidence of stunting in children, with p <0.05.